Pengalaman Tim Penggerak Pemberdayaan dan Kesejahteraan Keluarga dalam Pendampingan Kesiapsiagaan Pencegahan Kegawatdaruratan Demam Berdarah Dengue - Ferry Diana Karmilasari; Neni Oktavia; Ulva Hari Andini; Ratih Eka Fitrianingrum (Jurnal Keperawatan Florence Nightingale, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem that requires active community involvement in prevention and emergency preparedness efforts. The disease is caused by the dengue virus, transmitted by Aedes aegypti and Aedes albopictus mosquitoes that breed in clean water containers around households. This study aimed to explore the role of the Family Welfare Empowerment Team (PKK) in community empowerment for DHF prevention and emergency preparedness in Jepit Hamlet, Kaligondo Village, Genteng District. A qualitative study with a phenomenological approach was conducted. Participants were selected using purposive and snowball sampling techniques based on predetermined criteria. Data were collected through in-depth interviews with six PKK members actively involved in community health activities. Data analysis employed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing and verification. The findings identified four major themes: (1) optimization of the PKK’s role in community empowerment for DHF prevention; (2) enhancement of community preparedness through PKK assistance in DHF emergency management; (3) challenges in implementing DHF prevention and preparedness activities; and (4) strategies to strengthen the PKK’s role in DHF emergency prevention. The study concludes that the PKK plays a significant role in empowering communities through health education, community assistance, citizen engagement, and collaboration with healthcare professionals to improve DHF prevention and preparedness.